2020
DOI: 10.3389/fneur.2020.00583
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Social Media and Digital Devices Among Italian Neurologists

Abstract: 4 on behalf of the study group on "Digital technologies, web and social media" of the Italian Neurological Society

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 16 publications
2
21
0
Order By: Relevance
“…The problem here is that source of the content on social media platforms (YouTube, Facebook, Instagram etc.) is not inspected, most of them are not refereed or evidence-based [21,22]. Therefore, the content is not reliable.…”
Section: Plos Onementioning
confidence: 99%
See 2 more Smart Citations
“…The problem here is that source of the content on social media platforms (YouTube, Facebook, Instagram etc.) is not inspected, most of them are not refereed or evidence-based [21,22]. Therefore, the content is not reliable.…”
Section: Plos Onementioning
confidence: 99%
“…Therefore, the content is not reliable. In the study of Lavorgna et al (21), almost all physicians have encountered patients who had already made a self-diagnosis on the Internet before coming to see the doctors. The authors sets forth that physicians should warn their patients against incorrect/ unreliable information on the internet and recommend reliable online sources.…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…Recently, social networks using smart device such as smartphones and tablet terminal have become widespread and indispensable tool for patients and neurologists [11,12]. Furthermore, it has been suggested that this digitization process may be accelerated in the stroke care after a global emergency represented by the COVID-19 pandemic [13].…”
Section: Introductionmentioning
confidence: 99%
“…These barriers relate to training, technology issues, and acceptance by both health care practitioners and patients [ 10 ]. Indeed, a study that explored the views of health care practitioners (ie, neurologists) toward digital devices in clinical practice found that while the majority (95%) of the 405 participants used computers regularly at work, less than half (43.5%) used a tablet [ 11 ]. This suggests that one of the barriers to the uptake of technology may be acceptance from health care professionals.…”
Section: Introductionmentioning
confidence: 99%